A STUDY ON THE READING COMPREHENSION ABILITY ON REPORT TEXTS OF THE SECOND YEAR STUDENTS OF SMK MUHAMMADIYAH 2 PEKANBARU - Zul Dicara Al’asri; Rumiri Aruan; M. Syarfi M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The objective of this research was to find out the reading comprehension ability on report texts of the second year students of SMK Muhammadiyah 2 Pekanbaru. This is a descriptive research with only one variable. The data were collected from April to August 2018 by administering a test to the students in the form of multiple choice . The population of this research is the second year students of SMK Muhammadiyah 2 Pekanbaru. The sample was XI TKJ 2 (36 students) chosen by using cluster random sampling techniques. The findings of the research are as the following: finding main ideas (73.3), finding factual information (78.9), finding the meaning of vocabulary in context (82.2), finding reference (78.3), finding inference (78.9) and finding social function (80.6). As a conclusion, the highest score was in finding the meaning of vocabulary in context (82.2) which categorized into excellent level while the lowest score was in finding main ideas (73.3) which categorized into good level. Therefore, the writer recommended the students to improve their reading skills in order to get deep understanding of report texts and could reach excellent level.Key Words: Reading Comprehension, Ability, Report Text